PREOPERATIVE DENOSUMAB THERAPY IN PATIENTS WITH GIANT CELL TUMOR OF BONE - Vyrva, Oleg; Mikhanovskiy, Dmytro; Bitsadze, Marianna; Golovina, Olga; Danуshchuk Zinaida; Babych, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Giant cell tumor of bone (GCTB) is a benign osteolytic tumor with an aggressive course, affects the metaphyseal and epiphyseal areas of bone. GCTB is RANKL-positive tumor. Therefore, RANKL is a promising target for directed influence on the processes of bone resorption. Objective. To analyze the world and own experience of denosumab using in the treatment of patients with giant cell tumor of bone. Methods. The search for publications in electronic systems was carried out Google Scholar, PubMed, ScienceDirect, specialized archives journals and manuscripts. In addition, 57 patients with histologically verified GCTB without signs of malignancy were included. Results. Denosumab binds and inhibits RANKL, by stopping bone resorption by inhibiting differentiation, function and survival of osteoclasts. Information on the effectiveness of the drug in the treatment of patients with GCTB is contradictory. Some researchers claim that its use in the preoperative period reduces the amount of surgical intervention and the likelihood of recurrence of GCTB. The effect correlates with the duration of drug administration. Other authors report an increase in the percentage of local tumor recurrence with denosumab and the next performance of curettage. This is explained by the complexity of macroscopic determination of the boundaries changed by action tumor preparation and, accordingly, the difficulty of choosing reach for removal during surgery. Our own experience showed that neoadjuvant therapy with denosumab 120 mg on the 1, 8, 15, 28 days promotes the formation of clear boundaries of the tumor, its compaction and, consequently, reduces the risk of pathological fracture and allows ablastic tumor removal. Conclusions. The results of the study of the effect neoadjuvant therapy with denosumab is ambiguous. Under conditions its use followed by curettage increase the proportion of local recurrences of the tumor. At significant differences measures of lesions of GCTB before wide resection with endoprosthesis replacement administration of denosumab promotes bone formation skeleton around the tumor and its compaction, which allows ablastically remove it and reduce the risk of local recurrences.